2023
DOI: 10.1017/s0950268823001462
|View full text |Cite
|
Sign up to set email alerts
|

Assessing antimicrobial resistance in Campylobacter jejuni and Campylobacter coli and its association with antimicrobial use in Canadian turkey flocks

Rima D. Shrestha,
Agnes Agunos,
Sheryl P. Gow
et al.

Abstract: Turkeys are important sources of antimicrobial-resistant Campylobacter. A total of 1063 isolates were obtained from 293 turkey flocks across Canada between 2016 and 2021 to evaluate their antimicrobial resistance (AMR) prevalence, patterns, distribution, and association with antimicrobial use (AMU). A high proportion of C. jejuni and C. coli isolates were resistant to tetracyclines and fluoroquinolones, despite the very low use of these drugs. C. jejuni isolates had a higher probability of being resistant to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…The highest prevalence of resistance in both C. coli and C. jejuni isolates derived from chickens and turkeys was identified against tetracycline. This finding agrees with previous studies from North America and worldwide [ 9 , 11 , 14 , 15 , 32 ]. Tetracyclines are commonly used to treat and prevent bacterial poultry diseases [ 33 ], and the selection pressure of AMU is a major factor in the selection of tetracycline resistance.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The highest prevalence of resistance in both C. coli and C. jejuni isolates derived from chickens and turkeys was identified against tetracycline. This finding agrees with previous studies from North America and worldwide [ 9 , 11 , 14 , 15 , 32 ]. Tetracyclines are commonly used to treat and prevent bacterial poultry diseases [ 33 ], and the selection pressure of AMU is a major factor in the selection of tetracycline resistance.…”
Section: Discussionsupporting
confidence: 94%
“…The study results indicated that in both chickens and turkeys, C. coli isolates had higher AMR rates than C. jejuni isolates for most of the antimicrobials examined. This finding agrees with previous studies that described a higher proportion of MDR C. coli isolates from poultry [ 11 , 15 ]. In contrast, it was described that C. jejuni isolates have a lower rate of AMR, but they better survive the food processing environment that aids them to enter the food chain and infect humans [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations